Building performance and maintenance information model based on IFC schema - Marmo, Rossella; Polverino, Francesco; Nicolella, Maurizio; Tibaut, Andrej (Automation in construction, 2020)
The integration of operational information in building life-cycle management is a relevant topic within the facilities management domain. A previous study proposed a methodology based on Building Information Modelling (BIM) and Facility Management (FM) systems integration, underpinned by a Performance Information Model, to support the performance assessment and the maintenance management. The purpose of this paper is to extend and validate that methodology with an open standard approach. A subset of the Industry Foundation Classes (IFC) schema related to performance assessment and maintenance procedures is mapped into a relational database. The database supports the integration between BIM models and facilities information systems. Case studies including healthcare buildings test the database and a new application. The results contribute to the BIM adoption in the FM domain. Also, the studied and validated IFC schema subset can be considered as a contribution to the Model View Definition for FM. •This paper addresses a research gap which is moving from BIM to FM modelling.•An IFC compliant Performance Information Model (openPIM) is proposed.•A proof of concept is provided by case studies concerning healthcare facilities.•Enhanced FM competencies accomplished through comprehensive performance-based model